Exploration of fluorescent protein voltage probes based on circularly permuted fluorescent proteins - Gautam, Sunita G.; Perron, Amelie; Mutoh, Hiroki; Knopfel, Thomas (Frontiers in Neuroengineering, 2009)
Genetically-encoded fluorescent protein voltage sensors are promising tools for optical monitoring of the electrical activity of cells. Over the last decade, several designs of fusion proteins have been explored and some of them have proven to be sensitive enough to record membrane voltage transients from single mammalian cells. Most prominent are the families of VSFPs (Voltage Sensitive Fluorescent Proteins) that utilize the voltage sensor domain of Ci-VSP (Ciona Intestinalis voltage sensor-containing phosphatase). The voltage sensitivity of the fluorescence readout of these previously reported membrane potential indicators is achieved either via a change in the efficiency of fluorescence resonance energy transfer (FRET) between two fluorescent protein (FP) spectral variants or via modulation in the fluorescence intensity of a single FP. Here, we report our exploration on a third VSFP design principle based on circularly-permuted fluorescent protein (cpFP) variants. Using circularly-permuted EGFP derived from GCaMP2 and two newly generated circularly-permuted variants of the far-red emitting protein named mKate, we generated and characterized a series of voltage-sensitive probes wherein the cpFPs were fused to the voltage sensor domain of Ci-VSP. The most promising variants were based on circularly permuted mKate with new N- and C-termini given by residues 180 and 182. Even so their voltage sensitivity was relatively modest, they constitute a proof of principle for this novel protein design.